Photochemical Generation of a C5′‐Uridinyl Radical. Issue 16 (30th September 2015) - Shaik, Raziya; Ellis, Matthew W.; Starr, Matthew J.; Amato, Nicholas J.; Bryant‐Friedrich, Amanda C.
Abstract It has been postulated that sugar radicals and related species are involved in oxidative events involving RNA. To determine the contribution, if any, of these species to the deleterious effects of the endogenous exposome, it is important to unambiguously identify their degradation products. C5′‐Pivaloyl uridine was successfully synthesized and subsequently photolytically converted to a C5′‐uridinyl radical. Generation of the radical under anaerobic conditions in the presence of glutathione led to the formation of the expected reduction product, uridine. However, regardless of the presence or absence of reductant, the base elimination product, uracil, was also observed. Mass balances and product distributions were dependent upon the pH of the photolysis mixture. At low pH, trapping with glutathione successfully competed with base loss. These results indicate that this precursor should function efficiently in an investigation of the fate of the C5′‐uridinyl radical in RNA oligomers.